Assessing the Comorbidity Cycle Between Psoriasis and Addiction Based on ICD Coding in the Stockholm Psoriasis Cohort - Hannah Wecker; Axel Svedbom; Fabio Sánchez Orrego; Stefanie Ziehfreund; Mona Ståhle; Alexander Zink (Acta Dermato-Venereologica)
The comorbidity cycle between psoriasis and addictions remains unclear. The study aimed to investigate the cumulative incidence of addictions in psoriasis patients and controls in the Stockholm Psoriasis Cohort (SPC). The SPC is an observational cohort study that enrolled psoriasis patients between 2001 and 2005 and matched controls using the Swedish Total Population Register. Data were complemented by medical records from 1987–2013, focusing on 11 addiction diagnoses and the date of their assignment. Overall, 4,545 individuals (56.4% female; median age: 40) were included: 722 psoriasis patients and 3,823 controls. Patients showed 1.4 times (95% confidence interval: 0.98–1.98) higher odds of addiction diagnosis than controls. Alcohol dependency was the most common addiction diagnosis (78.2%), which was more frequent in patients than in controls (94.3% vs 73.6%, p = 0.009). Furthermore, patients showed 4.3 times (1.85–11.56) higher odds of receiving an addiction diagnosis after their initial psoriasis diagnosis than before. Results showed a tendency towards a higher risk of addiction in psoriasis patients, suggesting potential psoriasis-triggered addictive behaviour. Nevertheless, both substance abuse triggering psoriasis and chronic psoriasis inflammation triggering addictions have to be considered. In both cases, addictive behaviour needs to be addressed in psoriasis healthcare as a driver for poor disease outcome and comorbidities.